Penegakan Hukum Oleh Penyidik Polri Terhadap Tindak Pidana Penipuan Bermotif Investasi (Studi Kasus Di Polda Gorontalo) - Duhe, Rahmat; Darmawati, Darmawati; Haritsa, Haritsa (Fakultas Hukum Universitas Ichsan Gorontalo, 2026)
This research aims to assess the efforts of police in enforcing the law against investment-motivated fraud and to identify factors that hinder effective law enforcement in this area. The research employs an empirical method, specifically sociological legal study or field research, to capture the law in practice. The findings of this research reveal that: 1) Police efforts against illegal investment- motivated fraud include receiving public reports, conducting investigations, and transferring case files and suspects to the Prosecutor's Office for prosecution. 2) Obstacles to effective law enforcement against investment-motivated fraud include a limited number of personnel in Sub-Directorate 2 of Economy and Special Affairs, bank confidentiality issues, and insufficient reports by the public. Based on these findings, this research recommends increasing the personnel in Sub-Directorate 2 of Economy and Special Affairs and enhancing community engagement to improve the uncovering of case